CHARACTER EDUCATION TACTICS: STRATEGIES OF Civics TEACHERS IN STRENGTHENING CHARACTER EDUCATION IN SMA NEGERI 1 ARJASA KEPULAUAN KANGEAN KABUPATEN SUMENEP - Supriadi; Gunadi, Lie Epifani Rachmad; Anshori, Ibnu; Dhayinta, Shellya Tanaya (EDUCATUM: Scientific Journal of Education, 2024)
The implementation of character education in SMAN 1 Arjasa Kangean Islands faces quite dominant challenges, including geographical location, low level of parental education, and lack of parental support and understanding, thus also interfering with the effectiveness of character education efforts. This research is a field research, which is a type of research where researchers collect data and information directly in the field to explore the implementation of character education in students at SMAN 1 Arjasa. The findings of this study indicate that the implementation of character education at SMAN 1 Arjasa Kangean Islands is highly dependent on the role of Civic Education (PPKn) teachers. Teachers act as mentors, advisors, role models, and motivators for students by using various learning media to present the material in an interesting and effective manner. Teachers provide individual and group guidance, and provide examples of exemplary daily life, such as congregational prayer, handshakes, and environmental cleanliness, as a direct inspiration for students